1993
DOI: 10.1177/107554709301400301
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Policy Analysis by State Agency Officials

Abstract: Findings from a 1988 survey of U.S. state officials working in the areas of hazardous wastes, economic development, welfare, and education suggest that these officials do not appear to rely heavily on policy analysis from research organizations or from university faculty; instead, they rely principally on policy advice from their peers in other state agencies, newspapers, their counterparts in federal agencies, and staff from the governors' office. In attempting to understand knowledge utilization, the study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 20 publications
2
60
0
4
Order By: Relevance
“…This reflects prior research findings, which observed that public sector agencies were often distrustful about relying on external sources of expertise, preferring to draw on internal expertise and analyses instead (Hall & Jennings 2010;Lester 1993). A survey item that provided some insight into the types of linkages policy officials reported engaging in was one that captured the importance policy officials personally placed on specific strategies or activities for obtaining research information.…”
Section: Linkages Reported By Policy Officials Quantitative Findings mentioning
confidence: 94%
See 4 more Smart Citations
“…This reflects prior research findings, which observed that public sector agencies were often distrustful about relying on external sources of expertise, preferring to draw on internal expertise and analyses instead (Hall & Jennings 2010;Lester 1993). A survey item that provided some insight into the types of linkages policy officials reported engaging in was one that captured the importance policy officials personally placed on specific strategies or activities for obtaining research information.…”
Section: Linkages Reported By Policy Officials Quantitative Findings mentioning
confidence: 94%
“…Currently, as noted previously in this thesis, there is no universally accepted or widely adopted model for measuring the utilisation of research (Lester, 1993;Oh & Rich, 1996;Ouimet et al, 2010;Smith et al, 2011). The literature on the utilisation of academic research has, however, consistently suggested three broad types of use: instrumental, conceptual, and symbolic.…”
Section: Dependent Variable For Regression Modelsmentioning
confidence: 99%
See 3 more Smart Citations